A View From the Trenches: Interviews With Journalists About Reporting Science News. Issue 1 (February 2023) - Anderson, Josh; Dudo, Anthony
In the United States and many other large media markets, science journalism has experienced major structural shifts that have resulted in the profession largely being conducted by nonspecialists and freelancers who cope with an abundance of misinformation and a loss of public confidence. In this qualitative work, we present the results of in-depth interviews with science journalists to understand current struggles and motivations for producing science news. Despite structural challenges and occupational burnout, journalists are motivated to produce science news for their perceived social benefits. However, many of the ways they are left to cope with these issues are personal strategies (e.g., resilience) that are unsustainable and ignore systemic inequities.